Differential Effects of TGF-β2 on the Low-Density Lipoprotein Receptor Expression in Three Types of Human Subconjunctival Fibroblasts. (2nd January 2021) - Wang, Jiajian; Jiang, Chao; Jing, Qinghe; Jiang, Yongxiang; Shao, Tingting
ABSTRACT: Purpose : To investigate whether TGF-β2 had a different effect on the expression levels of low-density lipoprotein receptor (LDLr) in the subconjunctival fibroblasts from glaucoma patients who underwent a reoperation (RGSFs) compared with those from glaucoma patients who underwent first filtering surgery (GSFs) and control patients with cataracts (HSFs). Methods : Human subconjunctival fibroblasts were obtained from the three groups of patients. Different concentrations of TGF-β2 were added to the fibroblasts for 1, 3, and 5 days. The proliferation of the fibroblasts was determined by CCK-8 assays. Real-time PCR and western blotting were performed to analyze the mRNA and protein levels of LDLr. The uptake of DiI-labeled LDL was determined by confocal microscopy. Results : The results revealed that under TGF-β2 exposure, fibroblast proliferation was positively correlated with LDLr expression (all p < .001). The LDLr mRNA and protein levels were affected by TGF-β2 in a concentration-dependent and time-dependent manner in the RGSFs, GSFs and HSFs. The maximal expression of LDLr after TGF-β2 stimulation was consistent with the peak uptake of DiI-LDL, which was obviously highest in the RGSFs, followed by the GSFs, and then the HSFs (all p < .05). All 3 groups took up DiI-LDL in a similar time-dependent manner, with maximal uptake at 6 h following DiI-LDL incubation (all p < .05). In addition, there were significant differences in the LDLr protein levels in the subconjunctival tissues isolated from the glaucoma patients during reoperation, the glaucoma patients during first filtering surgery and the control patients at day 3 ( p < .05). The highest protein expression of LDLr was observed in the RG group. Conclusion : These data suggested that the RGSFs had the highest LDLr expression and the highest peak uptake of LDL among three groups. The LDLr-drug-LDL delivery system could potentially be used for targeted delivery of antimetabolite agents in anti-scarring therapy for glaucoma patients after filtering surgery.